Heterogeneity of cell membrane structure studied by single molecule tracking. (14th October 2021) - Mashanov, Gregory I.; Nenasheva, Tatiana A.; Mashanova, Alla; Lape, Remigijus; Birdsall, Nigel J. M.; Sivilotti, Lucia; Molloy, Justin E.
Abstract : We use total internal reflection fluorescence microscopy combined with super-resolution tracking of multiple individual molecules, in order to create high-resolution maps of local membrane viscosity. Abstract : Heterogeneity in cell membrane structure, typified by microdomains with different biophysical and biochemical properties, is thought to impact on a variety of cell functions. Integral membrane proteins act as nanometre-sized probes of the lipid environment and their thermally-driven movements can be used to report local variations in membrane properties. In the current study, we have used total internal reflection fluorescence microscopy (TIRFM) combined with super-resolution tracking of multiple individual molecules, in order to create high-resolution maps of local membrane viscosity. We used a quadrat sampling method and show how statistical tests for membrane heterogeneity can be conducted by analysing the paths of many molecules that pass through the same unit area of membrane. We describe experiments performed on cultured primary cells, stable cell lines and ex vivo tissue slices using a variety of membrane proteins, under different imaging conditions. In some cell types, we find no evidence for heterogeneity in mobility across the plasma membrane, but in others we find statistically significant differences with some regions of membrane showing significantly higher viscosity than others.